Do Gender, Socioeconomic Status and Regional Difference Predict the Reading Comprehension of English as a Foreign Language (EFL) Learners? - Karim, Abdul; Khemanuwong, Thapanee; Ferdous, Tanjila; Humaira, Tasnova; Sultana, Shahin; Ismail, Shaik Abdul Malik Mohamed (My University, 2024)
The current study examines the role of gender, socioeconomic status, and region in predicting the reading comprehension of English as a Foreign Language (EFL) learners. Based on the relevant literature, three hypotheses have been formulated, which entail three independent variables (gender, socioeconomic status, and region) and the dependent variable (reading comprehension) and were tested by employing a quantitative cross-sectional research method. The Thai Reading Evaluation and Decoding System (T-READS) test was administered to determine the participants’ reading comprehension scores. Approximately 730 male and female undergraduates at a Thai university with various socioeconomic statuses and regional diversity participated in this study. By conducting linear regression analysis, we predicted the role of gender, socioeconomic status, and region in predicting learners’ reading comprehension. The findings of the study revealed that gender, socioeconomic status, and region were not significant in predicting Thai university students’ reading comprehension. The pedagogical implications of the findings are also discussed.